The Effect of Training on Attributional Patterns among Nursing Students of Islamic Azad University-Birjand Branch - shahin taghi; Seyyed Abolfazl vagharseyyedin; seyyed Mohammad Ali Tabatabaiee; mahjoobeh goldanimoghaddam (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: Considering the effect of the attributional pattern on the individuals' behavior and feelings, nursing instructors should alter undesirable attributions that make students irresponsible toward learning activities. The current study was aimed to investigate the effect of attribution training on the attributional pattern among nursing students of Islamic Azad University-Birjand Branch in the academic year 2009-2010. Methods: In this quasi-experimental study, 187 nursing students in Birjand branch of Islamic Azad University were randomly assigned to control (n=93) and experimental (n=94) groups. At the beginning, using Julian Rotter’s locus of control Scale, participants' attributional patterns were evaluated. The experimental group received an attribution training program. Then, at the end of study, the students' attributional patterns were again reassessed. Data were analyzed using independent T, paired T, and McNemar's tests. Results: At the beginning of study, the mean attribution score showed an external locus of control pattern in both groups. At the end of the intervention, the mean attribution score of experimental group had decreased significantly (from 9.88±1.89 to 8.76±1.93), which indicated acquisition of an internal locus of control pattern among the experimental group. There was not significant change in the mean attribution score in the control group. There was a significant difference between the mean of score changes in the two groups. That is, the experimental group acquired a more internal locus of control pattern than the control group. Conclusion: It seems that attributional training could be considered for nursing students at the beginning of their admission to the university.